A Common Word Sebagai Narasi Toleransi Beragama di Indonesia - M Royyan Nafis Fathul Wahab; Al Mas'udah (Institut Agama Islam Al-Hikmah Tuban, 2022)
This research departs from the rampant narrative of intolerance in Indonesia, both distributed through social media and direct doctrine. A Common Word which is a response in the form of an open letter to Pope Benedict XVI's controversial statement regarding Islam which was agreed upon by 138 Muslim intellectuals and leaders in the world can be applied as a narrative of religious tolerance in Indonesia as a counter to radical doctrine. This study seeks to explore the values ​​contained in the A Common Word document that can be offered as a narrative of religious tolerance in Indonesia. This research is qualitative research based on the study of the text which is then presented descriptively. The findings in this study indicate that the values ​​contained in A Common Word such as clarification of prejudice, peace, justice, and love can be used as references for the tolerance movement, especially applying the Islamic values ​​of rahmatan lil alamin in Indonesia. Keywords: tolerance, religion, peace